Analiza rentowności polskich spółek pracowniczych - Kalinowski, Sławomir (Wydział Prawa i Administracji UAM, 1997)
The article presents an analysis of profitability of Polish ESOPs. The research conducted independently by IBnGR and ISP PAN and more general statistic data indicate higher profitability of ESOPs in comparison to other types of enterprises. There are two reasons for such a situation. Firstly, the best performing enterprises were included in the program of allowing employees to lease them. Secondly, ESOPs benefited from operational leverage effect much more extensively than other firms. The second, worth noting, feature of the profitability of Polish ESOPs is that in the period considered, it was growing less dynamicly than it was the case in other enterprises. This phenomenon is evident in research of the correspondence between GNP growth and gross profitability of ESOPs (and then all enterprises). This phenomenon can be, at least partly, explained by the, so called, additional expenditure burden borne by ESOPs. The stable level of profitability achieved by these enterprises indicates that their performance fall short of expectations that as a result of privatisation, they would be more effective and efficient. It is typical for Polish ESOPs that financial leverage has a significant impact on their rate of return on equity. Such an effect results from high operational profitability and high level of outside financing (especially, high amount of long-term accounts payable arising from outstanding leasing payments to the State Treasury). High rates of return from equity can become an incentive for prospective investors, who could be able to provide capital needed to solve the basic problem of all ESOPs: lack of financial resources necessary for further development.
The analysis of profitability of Polish ESOPs